RETROSPECTIVE STUDY OF MALARIA PREVALENCE IN SELECTED HOSPITALS IN ZARIA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
A retrospective study of laboratory records in selected hospitals in Zaria was carried out to determine the trend of malaria prevalence between 2001 and 2005. Data was obtained from the following selected hospitals: St Luke’s Anglican Hospital, Wusasa, Salama Infirmary, Saidu Dange railway Hospital and Sick Bay, Ahmadu Bello University, Main campus, Samaru. The selection of the hospitals was based on their geographical location and sizes. The prevalence was consistently high over the years; 2001–44.1%, 2002–59.45%, 2003–59.35%, 2004–58.30% and 2005–64.25%. There was no significant difference (P>0.05) between malaria infection in males and females. Infection rates were significantly higher in children than adults (P
Keywords: Retrospective, Malaria, Prevalence, Hospital, Zaria